Keys to educational success : teaching students with visual impairments and multiple disabilities - Zatta, Mary C.; Sacks, Sharon Z. (New York AFB Press, 2016)
Every student has unique learning needs, but addressing the diverse needs of students who have visual impairments and multiple disabilities can be particularly challenging for teachers. Keys to Educational Success helps educators unlock the learning potential of their students by providing key program strategies that can be directly applied to classroom learning routines. Keys to Educational Success is also an important reference for special education teachers, educational team members, and administrators
Keywords: Educación especial